Low Input Impedance Current Differencing Unit for Current Mode Active Devices Improved by Positive Feedback and ZC-CDBA Filter Application - Alaybeyoglu, Ersin; Guney, Arda; Altun, Mustafa; Kuntman, Hakan (IEEE, 2013)
In current mode analog circuit design, current differencing unit is widely used at the input stage of the current mode analog building blocks. The low input impedance current differencing unit is excellent for current mode circuit realization. In the current study, the positive feedback is used for reducing the input impedance of current differencing unit. The proposed current differencing unit is tested at the input stage of the ZC-CDBA (Z copy current differencing buffered amplifier) recently published as a current mode analog building block. The proposed circuit for ZC-CDBA is verified with the KHN analog filter application. The circuit simulations are verified by using BSIM3 0.18 mu m level-7 SPICE parameters.
Keywords: AMPLIFIER; DESIGN; Engineering